Pengaruh Program Affiliate Marketing, Harga, dan Promosi terhadap Keputusan Pembelian Parfum Mezuca di Tiktok Shop - Lensy Permatasari; Rafikhein Novia Ayuanti; Agung Pambudi Mahaputra (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the influence of affiliate marketing programs, price, and promotion on purchasing decisions for Mezuca perfume on TikTok Shop. As the digital era advances, social media platforms like TikTok serve not only as entertainment platforms but also as effective channels for marketing products through the TikTok Shop feature and affiliate programs. This strategy allows content creators to act as sales partners, directly influencing consumer decisions. This quantitative study utilizes primary data obtained through questionnaires distributed to 180 respondents who had purchased Mezuca perfume through Mamnun's TikTok Shop account. After a selection process using purposive sampling, 160 respondents met the criteria and were eligible for analysis. Data analysis was performed using SPSS software with various statistical tests, including descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²). The results indicate that affiliate marketing programs, price, and promotion simultaneously have a positive and significant effect on purchasing decisions. Partially, these three variables also show a significant positive influence on consumer decisions. These findings indicate that implementing effective digital marketing strategies, particularly through affiliate marketing, competitive pricing, and engaging promotions, plays a significant role in increasing consumer purchasing interest on social media platforms. This research offers practical implications for businesses in designing optimal and targeted digital marketing strategies.